Milk production and quality of a Jersey herd supplemented with a phytogenic additive (UNED Research Journal, 2025)
Introduction: The dairy sector faces a series of challenges that demand efficiency at both the productive and economic levels, aiming to improve zootechnical, health, and financial parameters. This includes the use of dietary ingredients that optimize the productive parameters of dairy cows. Objective: To evaluate the effect of a phytogenic additive on milk production and quality in grazing Jersey cows during the first 110 days of lactation. Methods: We selected 30 multiparous Jersey cows with an average of 3.0 lactations and an average production of 22.8kg/day in the previous lactation, assigned to two treatments with 15 replicates each: Treatment A (supplementation with 3.0g of PA) and Group B (control). The recorded information was analyzed using a generalized linear mixed model for repeated measures. Results: We observed that the use of a phytogenic additive did not result in statistically significant differences for the milk production variables (p=0.23), fat (p=0.75), crude protein (p=0.83), lactose (p=0.42), total solids (p=0.40), and milk urea nitrogen (p=0.44). Conclusion: We found no benefits in milk production and quality with this particular additive and conditions, but it still should be tested under other management conditions and production stages.
Keywords: total solid; fat; crude protein; milk urea nitrogen; Bos taurus; lactose